2003
DOI: 10.1111/1467-8276.00112
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Analysis of University Agricultural Biotechnology Patent Production

Abstract: This article examines the factors that account for agricultural biotechnology patenting success among universities using a dynamic count data model. It builds a theoretical and econometric model to capture the inherently dynamic and nonlinear process of technological innovation, wherein a feedback mechanism from previous success partially determines current patent counts. The econometric estimates reveal the importance to agricultural biotechnology patent production of land grant infrastructure, quality facult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 12 publications
4
32
2
1
Order By: Relevance
“…Moreover, the positive and significant influence of industrial funding on knowledge-transfer activities is also found in the empirical results of Powers (2003) and Di in the case of US universities. However, this result is contradictory to the findings of Payne and Siow (2003) and Foltz et al (2000) in terms of the effect of central government funding, and also contradictory to Foltz et al (2000), Foltz et al (2001) and Powers (2004) in terms of the effect of industrial funding. In this regard, this research might be seen as merely contributing to inconsistent empirical "confusion."…”
Section: The Relation Of Universities' Sources Of Funding To Knowledgcontrasting
confidence: 87%
See 3 more Smart Citations
“…Moreover, the positive and significant influence of industrial funding on knowledge-transfer activities is also found in the empirical results of Powers (2003) and Di in the case of US universities. However, this result is contradictory to the findings of Payne and Siow (2003) and Foltz et al (2000) in terms of the effect of central government funding, and also contradictory to Foltz et al (2000), Foltz et al (2001) and Powers (2004) in terms of the effect of industrial funding. In this regard, this research might be seen as merely contributing to inconsistent empirical "confusion."…”
Section: The Relation Of Universities' Sources Of Funding To Knowledgcontrasting
confidence: 87%
“…Payne and Siow (2003) also find that federal funding is significantly and positively related to the patent production of universities. However, in contrast to their results from previous a study in 2000, Foltz et al (2001 find that internal funding and state funding are positively and significantly related to patenting activities in the field of April/May 2011 |19 agricultural biotechnology, while industrial and federal funding are not. In a similar vein, Powers (2004) also confirms that industrial R&D support is not significantly related to university technology transfer.…”
Section: Determinants Of Knowledge-transfer Activities Of Universitiescontrasting
confidence: 84%
See 2 more Smart Citations
“…The first six (Foltz et al [26]; [27]; Carlsson and Fridh [13]; Payne and Siow [41]; Coupé [17]; Baldini et al [6]) use universities as a unit of observation, five in the US case and one in the Italian case. Two of them refer to the department or laboratory level of single European universities (Azagra et al [3], [4] The most frequent determinant included is R&D expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%